2014
DOI: 10.1002/lary.24446
|View full text |Cite
|
Sign up to set email alerts
|

Superior laryngeal nerve quantitative intraoperative monitoring is possible in all thyroid surgeries

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 29 publications
4
50
0
Order By: Relevance
“…However, the visual identification rate of EBSLN increased to 68.3% with the aid of IONM, which is close to the rates reported in the studies that included the routine division of strap muscles during superior pole dissection. In this study, the functional identification rate of EBSLN with IONM was noted to be 93.5%, which is threefold of the visual identification rate and in accordance with the rate of 83%-100% reported in other studies (2,8,10,11,15,23). We demonstrated that IONM provided a meaningful contribution to visual (p<0.001) and functional (p<0.001) identification of EBSLN.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, the visual identification rate of EBSLN increased to 68.3% with the aid of IONM, which is close to the rates reported in the studies that included the routine division of strap muscles during superior pole dissection. In this study, the functional identification rate of EBSLN with IONM was noted to be 93.5%, which is threefold of the visual identification rate and in accordance with the rate of 83%-100% reported in other studies (2,8,10,11,15,23). We demonstrated that IONM provided a meaningful contribution to visual (p<0.001) and functional (p<0.001) identification of EBSLN.…”
Section: Discussionsupporting
confidence: 90%
“…This connection has been described as the "human communicating nerve" and is known to contribute to the motor innervation of the thyroarytenoid muscle (25,27). The mean amplitude of EBSLN stimulation was significantly lower than that of RLN (10,15,25). Similar to these previous studies, we also achieved electromyographic responses from 74.4% of EBSLNs identified by IONM and the mean amplitude was 181±92 µV, which is lower than that of RLN (865±607 µV).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…EBSLN-elicited action potentials of the TAM are felt to be mediated by the human communicating nerve described earlier and virtually all cases are amenable to this monitoring technique as long as preoperative EBSLN function is intact and proper equipment set up is implemented (19,22). Also, intraoperative CTM EMG can be easily performed with subdermal EMG needle electrodes (37)(38)(39).…”
Section: Intraoperative Ebsln Identification and The Role Of Ionmmentioning
confidence: 97%
“…This so-called "human communicating nerve" is of special interest in intraoperative nerve monitoring (IONM) of the EBSLN, for it allows the recording of electroneuromyography (EMG) waveforms elicited by electrical stimulation by endotracheal surface electrodes (19). This finding is reinforced by several studies that found clear-cut TAM activity provoked by EBSLN stimulation in 70% to 100% of patients undergoing thyroid surgery (20)(21)(22)(23)(24). Darr et al (22) found that EBSLN-evoked potential of the TAM could be recorded in all cases when a tube with dedicated surface EMG electrodes in contact with the anterior aspect of the vocal cords was employed.…”
Section: Anatomy Of the Ebslnmentioning
confidence: 99%